Design and validation of an instrument to measure the level of knowledge in biosafety of dentist in times of COVID-19 - Mezarina Mendoza , Jhon Paul Iakov (2021)
Objective: To design and validate an instrument to measure the level of knowledge of dental surgeons about biosafety in dental care during the COVID-19 pandemic. Methods: Descriptive and cross-sectional study. Initially, an instrument was developed based on a 41-item bibliographic review. Content validation was carried out through the “expert judgment”. Five judges were selected who reviewed the formulation of the questions according to the criteria of relevance and clarity. Through the Aiken V test, 31 statements were obtained with the gathering of observations. Reliability was evaluated using a pilot test, with internal consistency determined with the Kuder Richardson test. Results: Two pilot tests were carried out, both groups were made up of 30 dentists including specialists and generals, as well as masters. In the first pilot a value of 0.519 was obtained in the Kuder Richardson coefficient, for which observations were raised, and in the second pilot study the value was 0.714, this value being considered adequate. Conclusion: The results obtained by the different ways to evaluate the test were adequate, obtaining an instrument of 22 items divided into five dimensions.